Braggart wom antecedent test with perceived support from other consumers as mediator - Evelyna, Feby; Azizah, Siti Nur (Institute of Computer Science (IOCS), 2024)
This research is to test the influence of C2C and active participation on braggart WOM by mediating support from other consumers on Sate Ambal Kebumen consumers. The sample for this research was 100 respondents who actively participated in training activities and shared experiences both online and offline. The results of the research show that active interaction influences the support felt by consumers, Active participation influences the support felt by consumers, C2C interaction influences WOM braggart, Active participation influences WOM braggart, Active participation influences WOM braggart, Support felt by consumers influences braggart WOM, Support felt by other consumers does not mediate the effect of C2C interactions on braggart WOM, Support felt by other consumers mediates the effect of active participation on braggart WOM. Theoretical and practical implications are explained in this article.